Robust distributed Nash equilibrium seeking for high-order systems with disturbances and coupling constraints - Chen, Yong; Li, Jiarui; Sun, Miaoping; Niu, Fuxi (Applied mathematics and computation, 2024)
The objective of this article is to tackle the problem of distributed searching for generalized Nash equilibrium (GNE) for high-order multi-agent systems (MASs) that are subject to external disturbances and coupling constraints. To address disturbances and linear equality constraints while ensuring that high-order agents achieve the task of seeking a GNE, a novel approach has been developed that utilizes gradient descent algorithms, extended state observers, and state feedback control. By utilizing the proposed algorithm, the agents' behavior will ultimately converge to a small range around the GNE points. The proposed algorithm's effectiveness is validated through two numerical simulations. •The article examines more complex higher-order dynamic systems.•The article considers both external disturbances and coupling equation constraints.•No need to know the specific model of the disturbance.